Mitigating server-side congestion in the Internet through pseudoserving - Kong, K.; Ghosal, D. (IEEE/ACM transactions on networking, 1999)
Server-side congestion arises when a large number of users wish to retrieve files from a server over a short period of time. Under such conditions, users are in a unique position to benefit enormously by sharing retrieved files. Pseudoserving, a new paradigm for Internet access, provides incentives for users to contribute to the speedy dissemination of server files through a contract set by a "superserver". Under this contract, the superserver grants a user a referral to where a copy of the requested file may be retrieved in exchange for the user's assurance to serve other users for a specified period of time. Simulations that consider only network congestion occurring near the server show that: (1) pseudoserving is effective because it self-scales to handle very high request rates; (2) pseudoserving is feasible because a user who participates as a pseudoserver benefits enormously in return for a relatively small contribution of the user's resources; (3) pseudoserving is robust under realistic user behavior because it can tolerate a large percentage of contract breaches; and (4) pseudoserving can exploit locality to reduce usage of network resources. Experiments performed on a local area network that account for the processing of additional layers of protocols and the finite processing and storage capacities of the server and the clients, corroborate the simulation results. They also demonstrate the benefits of exploiting network locality in reducing download times and network traffic while making referrals to a pseudoserver. Limitations of pseudoserving and potential solutions to them are also discussed.